The Influence of Sustainability Consciousness, Environmental Knowledge, and Green Purchase Intention on Marine Environmentally Friendly Behavior in Gen Z with Self Efficacy as a Mediator - Ardi Kurniawan; Nur Azizah; Salsabilla Rusydah Putri; Muhammad Daffa Bintang Setyawan; Muhammad Fariz Fadillah Mardianto (School of Postgraduate Studies, Diponegoro Univer, 2026)
Marine plastic pollution remains one of the most pressing environmental challenges, requiring greater public participation in marine conservation, particularly among Generation Z. Although previous studies have examined the influence of sustainability consciousness, environmental knowledge, and green purchase intention on pro environmental behavior, limited research has specifically investigated marine environmentally friendly behavior while simultaneously examining the mediating role of self-efficacy. Therefore, this study aims to analyze the influence of sustainability consciousness, environmental knowledge, and green purchase intention on marine environmentally friendly behavior among Generation Z, with self-efficacy as a mediating variable. A quantitative survey was conducted involving 194 Generation Z respondents, and the data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that sustainability consciousness, environmental knowledge, and green purchase intention have significant positive direct effects on marine environmentally friendly behavior. However, self efficacy does not significantly mediate these relationships. These findings suggest that cognitive and attitudinal factors play a more important role than self-efficacy in promoting marine environmentally friendly behavior among Generation Z. This study contributes to the growing literature on pro-environmental behavior by providing empirical evidence on the limited mediating role of self-efficacy in the context of marine environmental conservation and offers practical insights for designing environmental education and behavioral intervention programs targeting young people.